Usposobljenost likovnih pedagogov za poučevanje prostorskega oblikovanja pri likovni vzgoji - Duh, Matjaž (Revija za elementarno izobraževanje, 2008)
The article discusses the competency of art teachers in the field of spatial design. Current educational topics in undergraduate studies of Art Education do not give graduates the basic subject-specific competences for all areas of art education. By examining the curriculum for art education programs at the Faculty of Education in Maribor we learned that future art teachers are not introduced to spatial design subject material at all during their studies. The goal of our research, which included 73 art teachers, was to discover the teachers' views of spatial design and the kind of spatial design tasks they plan. The results obtained show that the current situation in elementary schools is alarming.
Keywords: vzgoja in izobraževanje; likovna vzgoja; prostorsko oblikovanje; likovni pedagogi; strokovna usposobljenost; izobraževanje učiteljev; osnovne šole